Uncommon Occurrences of Air Embolism: Description of Cases and Review of the Literature - Giorgio Berlot; Adriano Rinaldi; Marco Moscheni; Massimo Ferluga; Perla Rossini (Case Reports in Critical Care)
Many different risk factors have been associated with the occurrence of gas embolism making this potentially lethal complication easily avoidable. However, this condition can occur in circumstances not commonly reported. Three different and extremely uncommon cases of gas embolism are presented and discussed: the first was caused by the voluntary ingestion of hydrogen peroxide, the second occurred during a retrograde cholangiopancreatography, and the last followed the intrapleural injection of Urokinase. Whereas in the first patient the gas embolism was associated with only relatively mild digestive symptoms, in the remaining two it caused a massive cerebral ischemia and an extended myocardial infarction, respectively. Despite a hyperbaric oxygen therapy performed timely in each case, only the first patient survived. The classical risk factors associated with gas embolism like indwelling central venous catheters, diving accidents, etc. are rather well known and thus somewhat preventable; however, a number of less common and difficult-to-recognize causes can determine this condition, making the correct diagnosis elusive and delaying the hyperbaric oxygen therapy, whose window of opportunity is rather narrow. Thus, a gas embolism should be suspected in the presence of not otherwise explainable sudden neurologic and/or cardiovascular symptoms also in circumstances not typically considered at risk.